Religion in English Everyday Life : an Ethnographic Approach. - Jenkins, Timothy (Methodology and History in Anthropology Ser., 1999)
Starting from an ethnographic appraisal of the place of religious practices, and thereby returning to an approach more recently neglected, this book offers a detailed understanding of English everyday life. Three contemporary case studies - the life of a country church, an annual procession by the churches in a Bristol suburb, a range of linked "spiritualist" beliefs - disclose the complex patterns and compulsion of ordinary lives, including both moral and historical dimensions: the distribution of reputation and conflict, and the continuities of place and identity. At the same time, the approach revises previous accounts of English social life by giving a nuanced description of the construction of local lives in interaction with their wider setting. It demonstrates the creation of local particularity under an outside gaze, showing how actors create and cope with the forces of "modernity." In addition to the original ethnographic descriptions, the book also contributes to the history and theory of the study of complex societies.